2017
DOI: 10.1007/s00384-017-2851-3
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of 1495 patients with obstetric anal sphincter injuries referred for assessment of function and endoanal ultrasonography

Abstract: Third and fourth degree tears appear to be over diagnosed. Primary repair appears to be unsuccessful in the majority of cases. There appears to be poor correlation between objective and subjective assessment of sphincter function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…It has also been reported that on clinical examination alone, third-and fourth-degree tears are overdiagnosed in the labor ward [13]. In a retrospective review of prospectively collected data over a 10 year period from 1495 patients who had had a primary repair for sphincter injury, Thomas et al [13] found that endoanal ultrasonography demonstrated residual sphincter defect in 792 (53%) and normal sphincters, with no evidence of repair, in 661 (44%) patients. The majority of injuries involved both the external and internal sphincters (n = 501).…”
Section: Assessmentmentioning
confidence: 99%
“…It has also been reported that on clinical examination alone, third-and fourth-degree tears are overdiagnosed in the labor ward [13]. In a retrospective review of prospectively collected data over a 10 year period from 1495 patients who had had a primary repair for sphincter injury, Thomas et al [13] found that endoanal ultrasonography demonstrated residual sphincter defect in 792 (53%) and normal sphincters, with no evidence of repair, in 661 (44%) patients. The majority of injuries involved both the external and internal sphincters (n = 501).…”
Section: Assessmentmentioning
confidence: 99%
“…Appropriate sensibilization and training of childbirth professionals remains the mainstay for correct detection of OASIS following delivery. A proper detection of these lesions may depend on the experience of the assessor; structured hands-on workshops are important to improve health professionals’ abilities to identify and repair the internal sphincter correctly [ 28 , 29 , 30 ].…”
Section: Diagnosismentioning
confidence: 99%
“…The role of imaging in the early diagnosis of OASIS is further limited by the risk of incorrect interpretation of images and consequent potential overestimation of their occurrence [ 28 , 29 , 32 ]. Indeed, the detection rate of OASIS has significantly increased since the introduction of EAUS in the assessment of the anal sphincter following vaginal delivery (ranging from 11% to 36% of women), but it is unclear whether these findings represent clinically relevant defects [ 33 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Moreover, they found comparable Cleveland Clinic Fecal Incontinence scores between patients with or without a sphincter defect diagnosed with EUS. Likewise, Thomas and colleagues did not find a significant difference in Cleveland Clinic FI scores between patients with and without a sphincter defect detected by EUS [13]. Our aim was to investigate whether an association exists between anal sphincter defects detected by EUS and 3D-HRARM, and FI.…”
Section: Introductionmentioning
confidence: 86%